Studi Penambatan Molekuler Senyawa Tectoquinone Terhadap Enzim α-Glukosidase - Ahmad Najib; Rais Razak; Izzatul Fikril Mujtahid (Jurnal Fitofarmaka Indonesia, 2023)
The investigation focused on conducting an in silico screening of chemical compounds isolated from Syzygium oblanceolatum (C.B.Rob) to identify potential bioactive compounds that could act as inhibitors of α-Glucosidase. This screening involved tectoquinone as the potential inhibitor for α-Glucosidase and employed the Autodock Vina Docking process. The target enzyme, α-Glucosidase, was used as the receptor with 20 binding sites on the enzyme receptor 1LWJ and the Autodock Vina program was utilized for this purpose. The values of ∆Gbind and the lowest RMSD were determined for each of the 20 targeted binding sites on 1LWJ, representing the free energy change (∆G) resulting from the docking. The docking results demonstrated that the free energy change (∆G) for the 20 targeted binding sites ranged from -6.346 kcal/mol to -9.720 kcal/mol. The most favorable free energy change (∆G) was observed at the 16th binding site with a value of -9.720 kcal/mol, while the highest was recorded at the 18th binding site with a value of -6.346 kcal/mol.